Low-temperature condensation of carbonaceous dust grains from PAHs. Issue Volume 15:Issue S350(2019) (April 2019) - Gavilan Marin, Lisseth; Bejaoui, Salma; Gate, Gregory; Haggmark, Michael; Svadlenak, Nathan; de Vries, Mattanjah; Sciamma-O'Brien, Ella; Salama, Farid
Abstract: Interstellar carbon has been detected in both gas-phase molecules and solid particles. The goal of this study is to identify the link between these two phases of cosmic carbon. Here we report preliminary results on the low temperature formation of carbonaceous dust grains from gas-phase aromatic hydrocarbon precursors. This is done using the supersonic expansion of an argon jet seeded with aromatic molecules and exposed to an electrical discharge. We report experimental evidence of efficient carbon dust condensation from aromatic molecules including benzene and naphthalene. The molecular content of the solid grains is probed with laser desorption mass spectrometry. The mass spectra reveal a rich molecular composition including fragments of the parent molecule but also growth into larger molecular species.